2013
DOI: 10.1007/s00253-013-4962-2
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus surface layer proteins: structure, function and applications

Abstract: Bacterial surface (S) layers are the outermost proteinaceous cell envelope structures found on members of nearly all taxonomic groups of bacteria and Archaea. They are composed of numerous identical subunits forming a symmetric, porous, lattice-like layer that completely covers the cell surface. The subunits are held together and attached to cell wall carbohydrates by non-covalent interactions, and they spontaneously reassemble in vitro by an entropy-driven process. Due to the low amino acid sequence similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
196
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 215 publications
(212 citation statements)
references
References 194 publications
7
196
0
5
Order By: Relevance
“…Recently, the first extracellular glycoside hydrolase from L. acidophilus NCFM was shown to be a ␤-N-acetylglucosaminidase autolysin essential for cell division (40). This enzyme harbors a surface layer association protein (SLAP) domain (Pfam family PF03217 [41]) that confers noncovalent attachment to the proteinaceous outermost surface layer common in several lactobacilli (42). SLAP domains also occur at the C termini of other functionally important proteins such as autolysins, fibronectin and mucin binding proteins, putative peptidases, nucleases, and glycoside hydrolases as well as polysaccharide lyases according to the Pfam database (41).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the first extracellular glycoside hydrolase from L. acidophilus NCFM was shown to be a ␤-N-acetylglucosaminidase autolysin essential for cell division (40). This enzyme harbors a surface layer association protein (SLAP) domain (Pfam family PF03217 [41]) that confers noncovalent attachment to the proteinaceous outermost surface layer common in several lactobacilli (42). SLAP domains also occur at the C termini of other functionally important proteins such as autolysins, fibronectin and mucin binding proteins, putative peptidases, nucleases, and glycoside hydrolases as well as polysaccharide lyases according to the Pfam database (41).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition observed in the previous study may have resulted from an unspecific effect caused by the higher hydrophobicity of the BopA (lipo)proteins used in the study. Accordingly, the surface layer (S-layer) proteins of Lactobacillus, which are rich in hydrophobic amino acids (33), have been shown to inhibit the adhesion of S. aureus to Caco-2 cells (34). Furthermore, it has been shown that cell surface hydrophobicity indicates good adhesion potential for bacteria and that the high hydrophobicity of the cell surface of a probiotic strain correlates well with its capacity to inhibit pathogen adhesion through steric hindrance (35).…”
Section: Discussionmentioning
confidence: 99%
“…Some experimental data give hints that the proteases cleave peptide bonds in the peptidoglycan or the outer membrane of Gram-negative bacteria [41]. Another possible target are S-layer proteins, which comprise the outer cell border of many Archaea and Gram-positive bacteria, including lactic acid bacteria [22] [42] [43]. In this study, we found that the purified protease degrades S-layer proteins from L. brevis B 190, and previously, we demonstrated that the S-layer of Lactobacillus hilgardii B706 was degraded by the culture supernatant of S. albidoflavus B 578 [22].…”
Section: Discussionmentioning
confidence: 99%